WORK ENGAGEMENT EFFECTS ON JOB SATISFACTION AND TURNOVER INTENTION WITH GENERATION AS MODERATING VARIABLE - Utari, Kintan; Mustaqim, Mohammad (Jurnal Ekonomi dan Bisnis Airlangga, 2022)
Introduction: The focus of this study is to see how work engagement affects employees' job satisfaction and turnover intention within Generation X and Millennials. Methods: This study uses quantitative methods and data were collected by giving questionnaires to employees from different generations. Results: The results of this study are expected to give insight and solutions for the organization on how to understand work engagement for increasing job satisfaction and decreasing turnover intention among their employees. Conclusion and suggestion: Generation also does not provide a moderating effect on the relationship between work engagement and turnover intention. The existence of a non-significant relationship can be caused by a characteristic similarity between Generation X and Millennials.